Exergetic sustainability evaluation of horse manure biomass valorization by microwave pyrolysis. (1st September 2022) - Hosseinzadeh-Bandbafha, Homa; Fallahi, Alireza; Ghasemkhani, Hamid; Shafiei, Marzieh; Ghanavati, Hossein; Chong, Cheng Tung; Lam, Su Shiung; Tabatabaei, Meisam; Aghbashlo, Mortaza
Graphical abstract: Highlights: Microwave pyrolysis of horse manure biomass was analyzed using exergetic methods. Optimum conditions were selected by exergy, economic, and environmental factors. Reaction temperature markedly affected the exergy efficiency of the process. Catalyst quantity notably affected exergoeconomic and exergoenvironmental analyses. Temperature of 350 °C and catalyst:biomass ratio of 1:2 were optimal exergetically. Abstract: Microwave heating technique has gained widespread popularity in pyrolyzing biomass feedstocks due to its several unique features over the conventional furnace heating method. Accordingly, the present work aimed at finding the optimal operating conditions of a microwave reactor applied to pyrolyze horse manure from the exergetic, exergoeconomic, and exergoenvironmental viewpoints. The effects of two process variables, i.e., reaction temperature and catalyst:biomass ratio, were thoroughly investigated on the considered exergy-based methods. Three more key exergetic indicators "viz. exergy efficiency of the process, unitary exergoeconomic cost of the product", and unitary exergoenvironmental impact of the product were taken into account to select the most efficient, productive, and sustainable process conditions. The reaction temperature significantly affected the exergy efficiency of the process. Interestingly, the exergy dissipation due to mass loss and thermodynamic irreversibilities accounted for over 50% of the total input exergy of the process. The quantity of activated carbon catalyst is a determinant factor in exergoeconomic and exergoenvironmental analyses. The optimum operating conditions were the reaction temperature of 350 °C and the catalyst:biomass ratio of 1:2. Under these conditions, exergy efficiency of the process, unitary exergoeconomic cost of the product, and unitary exergoenvironmental impact of the product were 49.2%, 487 USD/GJ, and 151 mPts/GJ, respectively. Overall, it could be concluded that the applied exergetic approaches could be appealing complements to the chemical evaluation for analyzing and optimizing various bioenergy systems.